Sylvia’s Self-realization in Sarah Orne Jewett’s A White Heron From the Perspective of Deep Ecology - Zhu, Haiqing; Li, Yurui (Pacific International Journal, 2022)
In her short novel A white Heron, the famous American regional writer Sarah Orne Jewett pays attention to ecological problems. Sylvia, the protagonist of the novel, gradually realizes the significance of nature in the process of Self-realization. By living in the wood and befriending animals, she also changes from the stage of ego to social self and finally to ecological self. This process of Self-realization is a possible approach to the better relationship between human and nature.